Oficina de leirura e a formação do leitor : a recepção do texto literário por adolescentes de uma instituição não governamental do noroeste do Paraná - Cruz, Andréia Cristina (2008)
Nowadays, over one third of the Brazilian population is less than eighteen years of age. According to the last report on the children and adolescent situation, released by the United Nations Children's Fund (UNICEF) in August 2007 around 75% of these children and adolescents came from a poor family. The same report shows the risks and problems such as child labor, school dropout, marginalization, drugs, prostitution, violence and death that these people face. For this reason, there are many non-governmental organizations (NGOs) that somehow contribute, trying to improve these young people's lives. According to the National Secretariat for Social Assistance, currently there are in Brazil, around seventeen thousand NGOs duly registered and documented to assist approximately nine million young people. The fact that little has been studied about reading in these institutions encouraged us to make a research in a non-governmental organization located in the Northwestern of Paraná, the research has the objective of promoting the human being through reading strategies. It is known that in order to form a reader, both organization and commitment in several situations are required. Thus we can explain our study through the need and importance of diagnosing and reflecting upon the practice of reading developed by the NGOs. The methodology chosen was the qualitative research of ethnographic and applied nature. We have to consider how the literary texts will be accepted by the adolescent assisted by the organization. Therefore we carried out an analysis of the reading task which had been used followed by a Workshop on how to deal with reading in the organization. The diagnosis of the work on reading was made both by observation and questionnaires to be answered by the library assistant, by the Assistant of Communication of the Workshop and by the adolescents. In this diagnosis we realized that the organization is concerned with promoting reading among adolescents, however they need to invest on training and preparing those sponsible for applying reading. Based on the diagnosis and information on the Horizon Expectations of adolescents, we have planned a eading Workshop in accordance with the Receptional Method developed by Bordini and Aguiar (1988), following the theoretical assumptions concerning Reception Aesthetics. The workshop was implemented in a group of seventeen adolescents between eleven and thirteen years old, who participated actively in the activities proposed. Through the questionnaire about their Horizon Expectations, we found out that 100% of the adolescents enjoyed reading texts and declared that this kind of reading made them reflect upon their lives even though the reading was fiction. The reading of literary text then, highlighted the humanizing nature of the Literature that Antônio Candido (1972) deals with. This study on reading, mainly the diagnosis, contributed to considering other possibilities for working with reading, in addition, it contributed to improving the tutors' job. Currently, the coordinator is committed to signing an agreement with the city council so that they can provide some teachers from the regional administration to work at Escola Oficina Cidadão do Amanhã - _Workshop School Citizens of the Future.